Biopolymer composites: a review. Issue 1 (1st January 2021) - Aaliya, Basheer; Sunooj, Kappat Valiyapeediyekkal; Lackner, Maximilian
ABSTRACT: In spite of the fact that a prodigious portion of petroleum covers multitudinous products in the commercial world, its non-biodegradable characteristic is an unenviable factor. The utilization of biodegradable polymers or biopolymers is a prominent alternative to petroleum-based plastic products. Reinforcing natural fibers to biopolymer matrices significantly improves the properties of prepared plastic products. Such biopolymer composites have been developed by researchers to provide environmentally responsible materials and thereby reduce carbon footprint. Modification or functionalization of natural fibers is important to ameliorate the interfacial bonding with biopolymers, and to successfully obtain high-performance composite materials that can compete with conventional petrochemical-based polymer composite counterparts. Another widely accepted composite development technique is by combining different types of fibers into a single matrix to develop highly valued hybrid composites. The review focuses on the extraction, processing and characterization of bio-based materials; natural fibers and biopolymers, and their synergistic application and future scope as biopolymer composites in automotive and other growing sectors.